Reflection on innovation processes in a smallholder goat development project in Mozambique - Boogaard, Birgit K.; Swaans, Cornelis P.M.; Hendrickx, Saskia C.J.; Cosijn, M. (2013)
There is an increasing interest among researchers, practitioners and donors in using agricultural innovation system approaches to reach development outcomes. Limited practical experiences have been shared on the dynamics of these innovation processes and how project partners have dealt with that. The objective of this paper is therefore to share experiences from a smallholder livestock development project – the imGoats project in Mozambique – by reflecting on the dynamics of innovation processes in the project. The paper focusses on three intervention domains of the imGoats project: improving access to animal health services, improving market access and developing communal grazing areas. For each area, the innovation process was analysed by looking at the following elements: the local context, innovation type, actors involved, people taking the initiative, changing context, flexibility of project partners, pace of the process, and results. The findings demonstrate that the innovation processes of the three intervention domains varied considerably in terms of participation of actors, predictability of the process, expected and unexpected results and degree of experimentation. Hence, different innovation processes coexisted in the same project context, but were closely interrelated. Each addressed a particular constraint, which together contributed to the overall development objective of the project, though each innovation process was different. These findings and challenges have implications for research, practice and policy. For example, the dynamics of innovation processes may vary and depend on the intervention domain; this asks for a critical reflection on the role of research, facilitation and brokering in each of these cases. Hence, innovation processes require flexible management and should allow for joint experimentation and learning among project partners, stakeholders and decision makers; it also requires flexibility in project design and donor funding so that not only ‘obvious’ interventions are catered for, but also unforeseen developments.